Army and Navy ECHO Pain Telementoring Improves Clinician Opioid Prescribing for Military Patients: an Observational Cohort Study - Katzman, Joanna G. (J Gen Intern Med, 2018)
BACKGROUND: Opioid overdose deaths occur in civilian and military populations and are the leading cause of accidental death in the USA. OBJECTIVE: To determine whether ECHO Pain telementoring regarding best practices in pain management and safe opioid prescribing yielded significant declines in opioid prescribing. DESIGN: A 4-year observational cohort study at military medical treatment facilities worldwide. PARTICIPANTS: Patients included 54.6% females and 46.4% males whose primary care clinicians (PCCs) opted to participate in ECHO Pain; the comparison group included 39.9% females and 60.1% males whose PCCs opted not to participate in ECHO Pain. INTERVENTION: PCCs attended 2-h weekly Chronic Pain and Opioid Management TeleECHO Clinic (ECHO Pain), which included pain and addiction didactics, case-based learning, and evidence-based recommendations. ECHO Pain sessions were offered 46 weeks per year. Attendance ranged from 1 to 3 sessions (47.7%), 4–19 (32.1%, or > 20 (20.2%). MAIN MEASURES: This study assessed whether clinician participation in Army and Navy Chronic Pain and Opioid Management TeleECHO Clinic (ECHO Pain) resulted in decreased prescription rates of opioid analgesics and co-prescribing of opioids and benzodiazepines. Measures included opioid prescriptions, morphine milligram equivalents (MME), and days of opioid and benzodiazepine co-prescribing per patient per year. KEY RESULTS: PCCs participating in ECHO Pain had greater percent declines than the comparison group in (a) annual opioid prescriptions per patient (− 23% vs. − 9%, P < 0.001), (b) average MME prescribed per patient/year (−28% vs. −7%, p < .02), (c) days of co-prescribed opioid and benzodiazepine per opioid user per year (−53% vs. −1%, p < .001), and (d) the number of opioid users (−20.2% vs. −8%,p < .001). Propensity scoring transformation–adjusted results were consistent with the opioid prescribing and MME results. CONCLUSIONS: Patients treated by PCCs who opted to participate in ECHO Pain had greater declines in opioid-related prescriptions than patients whose PCCs opted not to participate. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11606-018-4710-5) contains supplementary material, which is available to authorized users.